Navigating supervision strictness in higher education: Directed towards freedom - Tom P. A. van der Pol (Högre Utbildning, 2025)
In an academic environment that increasingly values research supervision, but at the same time asks for rich scientific output and flashy results, determining the strictness of supervision offered to a PhD student is not straightforward. Both free and directive supervision come with benefits and pitfalls, which necessitates striking a delicate balance. The supervision dilemma is further complicated by the changing needs of both supervisee and supervisor during their education and career, respectively. In this in-depth discussion, explicitly taking into account the (young) supervisor viewpoint, the pros and cons of free and strict supervision are introduced by discussing excessive versions of these supervision styles. A way of navigating the free-to-directive supervision landscape is then proposed, while taking into account the archetypical goal of a PhD  education and the needs of a PhD student. It is argued here that PhD supervision should be directed towards freedom, according to the credo: as free as possible, as directive as needs be. The final section reflects on the role supervision seniority plays in the amount of freedom offered to the PhD student. This work critically reflects on supervision strictness in the modern-day PhD education, while aiming to assist (beginning) research supervisors in developing their supervision style.